1997
DOI: 10.1089/hum.1997.8.7-843
|View full text |Cite
|
Sign up to set email alerts
|

In VitroAssembly of SV40 Virions and Pseudovirions: Vector Development for Gene Therapy

Abstract: SV40 is an attractive potential vector with high-efficiency gene transfer into a wide variety of human tissues, including the bone marrow, a critical target organ for the cure of many diseases. In the present study, the three SV40 capsid proteins, VP1, VP2, and VP3, were produced in Spodoptera frugiperda (Sf9) insect cells. Their co-production led to spontaneous assembly of SV40-like particles. Nuclear extracts containing the three proteins were allowed to interact with purified SV40 DNA, or with plasmid DNA p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
30
1

Year Published

1997
1997
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(33 citation statements)
references
References 11 publications
2
30
1
Order By: Relevance
“…Forstova et al (1995) demonstrated that murine polyomavirus VP1 pseudocapsids generated from a recombinant baculovirus are able to transfer heterologous DNA efficiently into mammalian cells. More recently, SV40 pseudovirions self-assembled in insect cells have also been shown to be able to introduce foreign genes into mammalian cells (Sandalon et al, 1997). The current study demonstrates that human JCV VP1 is able to form pseudovirion and pseudocapsid particles when expressed in E. coli.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Forstova et al (1995) demonstrated that murine polyomavirus VP1 pseudocapsids generated from a recombinant baculovirus are able to transfer heterologous DNA efficiently into mammalian cells. More recently, SV40 pseudovirions self-assembled in insect cells have also been shown to be able to introduce foreign genes into mammalian cells (Sandalon et al, 1997). The current study demonstrates that human JCV VP1 is able to form pseudovirion and pseudocapsid particles when expressed in E. coli.…”
Section: Discussionsupporting
confidence: 53%
“…The size of DNA molecules packaged in viral particles after self-assembly in insect cells seems to vary. Sandalon et al (1997) showed that the capsid-like particles EE Self-assembly of JCV VP1 in E. coli Self-assembly of JCV VP1 in E. coli formed by SV40 VP1 expressed in insect cells can package various lengths of DNA in vitro, although the viral genome is about 5 kbp. One possible explanation is that eukaryotic DNA may associate with host histone proteins to form a minichromosome conformation.…”
Section: Discussionmentioning
confidence: 99%
“…Dithiothreitol, PMSF and the protease inhibitor cocktail were added to the buffer immediately before use. 14,15 Nuclear extract concentration was measured using the BCA Protein Assay protocol (Pierce, Rockford, IL). The nuclear extract was kept for more than a year at À201C.…”
Section: Preparation Of Nuclear Extracts From Sf9 Cellsmentioning
confidence: 99%
“…Since then, progress has been made in the use of polyomavirus capsid as a gene delivery vector. [18][19][20][21][22][23][24][25][26][27] However, the efficiency of gene transduction using polyomavirus vector is low. In part, this may have been caused by inefficient DNA packaging.…”
mentioning
confidence: 99%